Spreading the words of Spore - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Mehari Abay of Mekele, Ethiopia writes: 'I have been translating at least the first article of Spore into the local language Tigrigna and sending it to the local radio broadcasting service, sharing the idea with others'. Spore really welcomes this...